Peran Guru Pak Dalam Menggunakan Media Sosial Belajar Mengajar Bagi Peserta Didik di SDN Tapin Bini 1 - Frenika Evalina; Yosia Belo (Jurnal DIKMAS, 2024)
Online social media has a very positive influence on students at SDN Tapin Bini 1 for smooth teaching and learning activities because they can get various data related to learning material, interactions with fellow friends, for entertainment, and various other important information. For this reason, PAK teachers need to provide students with a proper understanding regarding the responsible use of social media. If PAK teachers are not serious about providing proper understanding, students will misuse social media, for example making fun of their friends, spreading fake news, deceiving friends, and so on. This article aims to explain the role of PAK teachers in making good use of social media for students so that social media can be used to communicate more widely due to the ease of facilities in disseminating good information. The research method used is qualitative through observation, interviews and documentation approaches. The results of this research are that PAK teachers must care more about students in providing an appropriate understanding of the use of online social media, so that it can be useful for teaching and learning activities carried out, both at school and doing assignments at home.